Efektifitas Metode Demonstrasi dalam Meningkatkan Keterampilan Membuat Smoothies bagi Anak Tunarungu - Septiana Ginting; Zulmiyetri Zulmiyetri (Jurnal Penelitian Pendidikan Khusus, 2018)
This article  is backgrounded over instant drinks consumption (pop ice) discovery and dearth of making smoothies ability by deaf students of 11th grade,  SLB N 1 Padang. This research has a purpose to prove that demonstration method is an effective way to increase smoothies-making skills for deaf students.  This research uses experimental method in One Group Pretest-Posttest Design of Quasy Experiment style.  This research is started by doing pretest, then using demonstration method treatment, and ended by doing posttest. Their result of doing pretest and posttest activity is compared and processed by using Mann Whitney's formula test.  The result shows that their ability in making smoothies is around 48% at pretest, while on posttest attains 74%. Then the data is scientifically processed by using Mann Whitney's formula and obtained; U-hit is three and U-tab is two with five samples at 95 significant degrees and alfa is 0.05. Thus, hypotheses can be accepted because U-hit is bigger than U-tab and it's proven that demonstration method is an effective way to increase smoothies-making skills for deaf students. There is a suggestion for the school that if they are willing to use demonstration method to increase smoothies-making skills for deaf students.